The Challenges of Global Public Health Amid the COVID-19 Pandemic: A Mini-Review - Ashraf, Asfa; Iqbal, Muhammad Naeem; Irfan, Muhammad; Muhammad, Ali; Shahzad, Mirza Imran (PSM Biological Research, 2020)
The COVID-19 is presenting novel challenges for global primary healthcare, and its response has been inspiring, varied, and troubling. The pandemic is a transnational threat that requires a global response, the outbreak exposed broader structural weaknesses in the global healthcare system. The public healthcare systems are experiencing varying levels of strain amid rising infection rates. The world governments are taking radical mitigation measures to counter the health impact of the virus, which on the other hand has severe economic and financial consequences on the lives of the people around the world. We must ensure equal access for all to care for physical and mental health and advocate for the role of primary care at an individual, local, national and international level in managing COVID-19 and its long-term impact as well as routine public healthcare.